mRNA export: threading the needle - Germain, Hugo; Gaouar, Ouassila (Frontiers in Plant Science, 2013)
After mRNA biogenesis, several proteins interact with the messenger to ensure its proper export to the cytoplasm. Some of these proteins will bind RNA early on, at the onset of transcription by RNA polymerase II holoenzyme, while others will join later for downstream processing steps, such as poly-adenylation or splicing, or may direct mRNA ribonucleoprotein particle migration to the nucleopore. We recently discovered that Arabidopsis plant knockout for the protein MOS11 (MODIFIER OF SNC1, 11) partially suppresses auto-immune responses observed in the TNL-type R gene gain-of-function variant snc1 (suppressor of npr1-1, constitutive 1). This suppression of resistance to pathogens appears to be caused by a decrease in nuclear mRNA export in mos11-1 snc1 plants. In humans, the putative orthologue of MOS11, CIP29, interacts with three proteins that are also involved in mRNA export: DDX39 (DEAD-box RNA helicase), TAF15 of the FUS family (FUSED IN SARCOMA) and ALY (ALWAYS EARLY), a protein implicated in mRNA export in mammalian systems. These proteins have received very little attention in plants. Here, we will discuss their particularities and role in mRNA export and biotic stress.